Internet-Based Cognitive Behavioral Therapy for Informal Caregivers: Randomized Controlled Pilot Trial - Biliunaite, Ieva; Kazlauskas, Evaldas; Sanderman, Robbert; Truskauskaite-Kuneviciene, Inga; Dumarkaite, Austeja; Andersson, Gerhard (JMIR Publications, 2021)
BackgroundCaregiving for a family member can result in reduced well-being for the caregiver. Internet-delivered cognitive behavioral therapy (ICBT) may be one way to support this population. This is especially the case for caregivers in countries with limited resources, but high demand for psychological services. ObjectiveIn this study we evaluated the effects of a therapist-guided 8-week-long ICBT intervention for informal caregivers. MethodsIn total, 63 participants were recruited online and randomized either to the intervention or to the wait-list control group. The main study outcome was the Caregiver Burden Inventory (CBI). Secondary outcomes included measures of caregiver depression, anxiety, stress, and quality of life. ResultsModerate between-group effect sizes were observed for the CBI measure, in favor of the intervention group, with a Cohen d=-0.70 for the intention-to-treat analysis. Analyses of the subscales of the CBI showed significant reductions on the subscales of Development and Physical Health. Moderate reductions were found for depression and anxiety scores as indicated by the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) scores. Large between-group effects were observed for reduction in stress and increase in quality of life as indicated by the Perceived Stress Scale-14 (PSS-14), The Brunnsviken Brief Quality of Life Scale (BBQ), and The World Health Organization-Five Well-Being Index (WHO-5). In addition, participants experienced little to no difficulty in using the program and were mostly satisfied with the intervention's platform and the choice of content. ConclusionsThis is the first internet intervention study for informal caregivers in Lithuania. The results suggest that therapist-guided ICBT can be effective in reducing caregiver burden, anxiety, depression, stress, and improving quality of life. Trial RegistrationClinicalTrials.gov NCT04052724; https://clinicaltrials.gov/ct2/show/NCT04052724